Membrane Electrode Assembly Based on Sulfonated Polysulfone-Activated Zeolite Composite Membrane for Fuel Cell Applications - Sri Mulijani; Yoki Yulizar; Armi Wulanawati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
The depletion of fuel cell reserves shows the need for alternative energy sources. In this context, fuel cells provide a promising solution, generating power without emissions. The membrane electrode assembly (MEA) in fuel cells is a critical component to maximize combustion efficiency. Therefore, this study aims to develop MEA using a composite membrane based on sulfonated polysulfone-activated zeolite (PSfs-Z). The membrane was obtained by first sulfonating polysulfone (PSf) and then adding activated zeolite. Optimum fuel performance was achieved with the activated zeolite using 3 N HCl. Sulfonation was completed, as demonstrated by a sulfonation degree of 32.63%. The absorption bands of the SO2 group vibration from SO3H of PSfs were identified at a wave number of 1111.00 and 1259.33 cm−1. The successful formation of MEA was confirmed by its morphology, as observed using a scanning electron microscope, with the formation of a catalyst layer and a membrane in the cross-section. The highest proton conductivity and cell potential obtained for PSfs-Z 3 N MEA were 0.01727 S.cm−1 and 330 mV, respectively. This means the membrane electrode assembly based on a sulfonated polysulfone-activated zeolite composite membrane has a higher potential than the